Penguatan Kapasitas Desa Melalui Penyusunan Masterplan Desa Jembayan Tengah Kabupaten Kutai Kartanegara - Lukman Priyandono; Lorensius Lorensius (Communio: Jurnal Pengabdian Kepada Masyarakat, 2022)
The village master plan is a document that can be a guide in determining the direction and development of a village, with all the potential that exists, Jembayan Tengah Village does not yet have a master plan that can be a guide and development scheme in managing village potential and minimizing existing obstacles. This preparation activity aims to assist residents in understanding the potential values ​​of the village and directing its development in realizing the aspirations and expectations of the residents. The method of preparing this village master plan uses a comprehensive approach, flexibility, spot strategy (direct observation), and a literature approach. Based on a series of analyses and concepts on the potential and constraints that exist in the village, it can be concluded that the opportunity has the potential to become a tourist village. There are peculiarities or characteristics that can be developed towards economic independence and potential characteristics that can be developed are agro-tourism villages. The potentials are strategic riverbanks, river docks, fishery centers, agricultural land, klulut honey educational tours, forest conservation, and the natural roaming environment, outbound game arenas, campgrounds, village markets as shopping centers, village study centers, and socio-cultural potential. Jembayan Tengah Village will grow and develop according to the existing potential with a strong commitment to making it happen with the residents. This village master plan document can be a guide and direction for the gradual implementation of development.